Effects of exogenous enzymes and application method on nutrient intake, digestibility and growth performance of Pelibuey lambs - López Aguirre, Daniel; Hernández Meléndez, Javier; Rojo, Rolando; Sánchez Dávila, Fernando; López Villalobos, Nicolás; Salem, Abdel-Fattah Z. M.; Martínez González, Juan Carlos; Vázquez Armijo, José Fernando; Ruíz, Salomón (SpringerPlus, 2016)
Pelibuey sheep is the main breed in the tropical and subtropical regions of Mexico, and high demand of sheep meat has favored the finishing of lambs in feedlots with diets containing high levels of grains. The objective of this study was to evaluate the effects of exogenous enzymes (EE) and application method on nutrient intake and digestibility and performance of growing Pelibuey lambs. Treatments were based on comparison of two different methods of adding an enzyme product (sprayed on the total mixed ration or applied orally to the lambs) versus control treatment (no added enzyme). Twenty-one Pelibuey lambs, weighing 15.7 kg (SD = 1.8 kg) initial body weight, were individually housed in shaded pens and assigned randomly to one of the three enzyme treatments. At the end of study (lasting for 45 days), three lambs from each treatment were randomly selected and adapted to a pants and harness designed for fecal collection to measure nutrient digestibilities. Total body gain and average daily gain were affected (P < 0.05) by supplemental EE. The application method of EE had significant (P < 0.05) effect on FCE and FCR, but no effects were observed on nutrient intake. Supplemental EE did improve (P < 0.05) the digestibilities of dry matter, organic matter, neutral and acid detergent fiber, but no differences were observed in crude protein digestibility. The application method of EE had significant (P < 0.05) effect on the digestibility of acid detergent fiber. Supplemental EE can improve body weight gain and nutrient digestibilities without affecting nutrient intake in Pelibuey lambs, but the results of feed conversion efficiency and acid detergent fiber digestibility depend on the application method used of the EE